Design and implementation of web product search engine (part 1) - Chua, Billy Wee Ren. (2010)
The convenience of online shopping on the Internet encourages online businesses to expand their range of products and to deliver customer-oriented services to serve online shoppers better. This project will study on product search using images and explores the different types of Image Retrieval Engine which will complement with existing Web Product Search Engine.